(untitled) (Cultura Económica, 2025)
This paper analyzes the process of nationalization of the British railways in Argentina between 1946 and 1948, during the early years of the government of Juan Domingo Perón. Through a critical review of primary and secondary sources, this work examines the economic, political and international factors that influenced the decision of the Argentine government to directly acquire such railways. This research highlights the contrasts between planning and improvization, sovereignty and foreign influence and provides a broad view of this purchase in the context of post-war state interventionism and the economic relations between Argentina and the United Kingdom.